The kiss curse : a novel - Sterling, Erin ([Ex Hex, 2022)
"Gwyn Jones is perfectly happy with her life in Graves Glen, Georgia. She, her mom, and her cousin have formed a new and powerful coven; she's running a successful witchcraft shop, Something Wicked; and she's started mentoring some of the younger witches in town. As Halloween approaches, there's only one problem--Llewellyn "Wells" Penhallow. Wells has come to Graves Glen to re-establish his family's connection to the town they founded as well as to make a new life for himself after years of being the dutiful son in Wales. When he opens up a shop of his own, Penhallow's, just across the street from Something Wicked, he quickly learns he's gotten more than he bargained for in going up against Gwyn. When their professional competition leads to a very personal--and very hot--kiss, both Wells and Gwyn are determined to stay away from each other, convinced the kiss was just a magical fluke. But when a mysterious new coven of witches come to town and Gwyn's powers begin fading, she and Wells must work together to figure out just what these new witches want and how to restore Gwyn's magic before it's too late"--Page 4 of cover.